Appetibility and effect of neem (Azadirachta indica) leaf foods on weight performance and viability of preweaning rabbits (Oryctolagus cuniculus). - Vidjannagni, Delphin Sévérin; SEIBOU TOLEBA, Soumanou; SINA, HAZIZ; Mahamadou, Dahouda; Adenile, Adam; Natonnagnon, Ulrich; Daga, Florian Dadjo; Harouna, Aminatou; Baba-Moussa, Lamine (My University, 2018)
The aim of this study was to evaluate the possibility of using neem (Azadirachta indica) leaves in the feeding of lactating rabbits. For 35 days, food consumption, weight performance and mortality were recorded in 96 mother cages of four batches of lactating rabbits subjected to four diets, including a control diet without neem leaves (lot 0) and three diets (lot 5: 5% leaves; lot 10: 10% leaves, and lot 15: 15% leaves) containing dried leaves of neem at different concentrations. The mean dietary intake of the animals of lot 15 (167.20 g/day/cage) was significantly lower than that of lot 0 (206.29 g/day/cage). Ingestions recorded in C3 litter class (7 to 9 rabbits) were higher (P<0.05) than those in C1 (1 to 3 rabbits) and C2 (4 to 6 rabbits). The initial mean weights of the young rabbits from lot 15 were significantly higher (P<0.05) than those of lot 5. No difference was observed between the birth-weaning of the four lots. The growth rate of young rabbits from females belonging to the C1 litter class (17.30 g/day) was higher (P˂0.01) than that of young rabbits whose litters were higher than 7 rabbits (8.82 g/day). The birth-weaning mortality rates of lot 0 (12.50%) and 5 (18.30%) were similar (P˃0.05). It was the same (P˃0.05) for batches 10 (37.60%) and 15 (34.30%). The incorporation of the neem leaves can be considered to increase the cost-efficacy during breeding rabbits.
Keywords: Oryctolagus cuniculus; Azadirachta indica; ingestion; growth rate; mortality.